PERSEPSI PENERAPAN UU HPP DAN TAX COMPLIANCE: PERAN MEDIASI KEPERCAYAAN KEPADA PEMERINTAH - Riyanti, Budi; Riana, Anita (ITB AAS INDONESIA, 2024)
Indonesia has a tax ratio of around 10%, this is less than optimal in ensuring the availability of money for sustainable development. To increase tax compliance, various efforts have been made by the government, including issuing a tax harmonization law which is a form of tax reform and promotes the principle of tax justice, However, amidst the government's hard efforts to increase tax compliance, a number of unscrupulous employees of the Directorate General of Taxes actually harmed the government's efforts by a number of corruption cases emerging. The purpose of this study is to analyze the influence of perceptions of the implementation of UU HPP on tax compliance, how the perception of implementing UU HPP influences trust in the government, how government trust influences tax compliance and to analyze how trust in the government mediates the relationship between perceptions of implementation. UU HPP on tax compliance. The population and sample for this study are MSME Taxpayers in the city of Salatiga. The research sample was calculated using the lemeshow formula with a margin of error of 10%, so the minimum sample size is 99.38 so it is rounded up to 100 respondents. The analysis technique for this research uses the Smart Partial Least Square (PLS) 3.0 tool. The results of the study show that perceptions of UU HPP implementation are positively correlated with tax compliance, perceptions of UU HPP implementation are positively correlated with trust in the government, trust in the government is positively correlated with tax compliance, and trust in the government can mediate the relationship between perceptions of UU HPP implementation and tax compliance.